2018
DOI: 10.2174/1871520617666170522124711
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Antibacterial Cubane-based Nanocomposite and its Application in Combination Cancer Therapy

Abstract: It was concluded that this novel cubane based drug delivery vehicle could process antibacterial and anticancer therapeutics spontaneously, representing promising tumor targeted system in nanomedicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Previous studies proved antibacterial properties of different polymeric nanocomposites with cationic blocks. 28 - 30 , 32 , 54 In order to investigate the probable antibacterial ability of prepared nanocomposites, their antibacterial tests were performed against the standard microbial strains of P. aeruginosa and E. coli ( Table 2 ). The mentioned bacteria were treated with OLPALg, OMTALg, CIP/OLPALg and CIP/OMTALg nanocomposites with various concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies proved antibacterial properties of different polymeric nanocomposites with cationic blocks. 28 - 30 , 32 , 54 In order to investigate the probable antibacterial ability of prepared nanocomposites, their antibacterial tests were performed against the standard microbial strains of P. aeruginosa and E. coli ( Table 2 ). The mentioned bacteria were treated with OLPALg, OMTALg, CIP/OLPALg and CIP/OMTALg nanocomposites with various concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The newly developed multifunctional OLPALg and OMTALg nanocomposites have a cationic segments containing imidazolium ionic liquid segments intercalated in Laponit-RD and montmorillonite. Previous studies proved antibacterial properties of different polymeric nanocomposites with cationic blocks [28][29][30]32,54 . In order to investigate the probable antibacterial ability of prepared nanocomposites, their antibacterial tests were performed against the standard microbial strains of Pseudomonas aeruginosa (p. aeruginosa) and Escherichia coli (E. coli) ( Table 2).…”
Section: In-vitro Antibacterial Activity Of Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4-Disubstituted cubanes have produced a bigger impact in SAR studies examining their use as a linker, allowing for comparison to simple cyclic spacers, such as cyclobutane or cyclohexane, and polycyclic residues such as bicyclo[1.1.1]pentane (72), bicyclo[2.2.2]octane (73), adamantane (74), and bicyclo[2.2.1]heptane (75) (Figure 9). Compounds 76 were analyzed for nonspecific binding, and the results obtained showed that the 72-linked compound 76c had a much lower propensity for nonspecific binding compared to 76a, 76b, and 76d.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“… Compound 66 has also been developed as a polymerization precursor. Subjecting 66 to free radical copolymerization with various drugs leads to novel and targeted delivery systems. Nitroxyalkyl groups substituted onto cubane with various linkers have been developed and explored for their anti-ischemic activity (compounds 67 ) . Compound 67a showed an improved ratio between the necrotic and ischemic zones (36.1%) when compared to the lead compound nicorandil ( 68 , 42.0%), where a mononitroxyalkyl is substituted on a pyridine.…”
Section: 4-disubstituted Cubanesmentioning
confidence: 99%